Changes in the microbiome of the sea anemone Exaiptasia diaphana during bleaching from short-term thermal elevation - Sydnor, Jamison R.; Lopez, Jaime; Wolfe, Gordon V.; Ott, Lisa; Tran, Cawa (Frontiers in Marine Science, 2023)
We examined the response of microbial communities in the model sea anemone Exaiptasia diaphana (Aiptasia) to short-term thermal elevation. Through 16S rRNA gene sequencing, we characterized the microbiomes of symbiotic (with algal symbionts) and aposymbiotic (bleached) anemones under ambient (27°C) and heat-stressed (34°C) conditions for 8-10 days, using both replicated endpoint and non-replicated time-course approaches. Consistent with prior studies, we observed a stable abundance of bacteria from the families Alteromonadaceae and Rhodobacteraceae, though with wide variation among individual anemones. We observed that symbiotic state conferred a larger impact on the microbiome than heat stress, implying the microbiome may play a metabolic role in the maintenance of cnidarian-dinoflagellate symbiosis. In particular, Pelobacter, an anaerobic sulfate-reducer that is also a potential nitrogen fixer, was present only in symbiotic anemones, and its abundance decreased with initial exposure to 34°C, but recovered after 7 days. In aposymbiotic anemones, the added heat stress appeared to result in a large increase of rare bacterial taxa, which included potential pathogens such as Vibrio following bleaching. We also observed several archaea, the first reported for this model, but only in the seawater surrounding aposymbiotic Aiptasia, where abundance increased dramatically following heat stress. We further explored the diazotrophic (nitrogen fixation) potential of diverse bacteria associated with symbiotic and aposymbiotic Aiptasia, under both ambient and heat-stressed conditions, using nifH-PCR and qPCR and the acetylene reduction assay (ARA). In contrast to some stony corals, nifH was barely expressed in both anemone types, and under ambient conditions, diazotrophic activity was not detectable via ARA. Thus, although this research contributes to the growing knowledge of the bacterial community associated with a prominent model used in coral-symbiosis research, our results also suggest using caution when making direct comparisons between Aiptasia and different coral species in microbiome studies.